👤
a fost răspuns

Să se descompună in factori scoțând factor comun:
a)2x(x+1)-5(x+1)
b)4(2x+3)-x(2x+3)
c)6x(3x-7)+5(3x-7)
d)6x(4x-1)-2(4x-1)


Răspuns :

a) 2x(x+1)-5(x+1) = (x+1)(2x-5)

b) 4(2x+3)-x(2x+3) = (2x+3)(4-x)

c) 6x(3x-7)+5(3x-7) = (3x-7)(6x+5)

d) 6x(4x-1)-2(4x-1) = 2(4x-1)(3x-1)

Factor comun la toate.
a. 2x (x+1)-5 (x+1)=(x+1)(2x-5)
[tex]b.4(2x + 3) - x(2x + 3) = (4 - x)(2x + 3)[/tex]
[tex]c.6x(3x - 7) + 5(3x - 7) =( 6x + 5)(3x - 7)[/tex]
[tex]d.6x(4x - 1) - 2(4x - 1) = (6x - 2)(4x - 1) =
2(3x - 1)(4x - 1)[/tex]